2008
DOI: 10.17221/1984-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic testing of different stages of avian tuberculosis in naturally infected hens (Gallus domesticus) by the tuberculin skin and rapid agglutination tests, faecal and egg examinations

Abstract: Avian tuberculosis (ATBC) is a significant cause of morbidity and mortality in birds in zoos and breeding establishments. The primary sources of Mycobacterium avium subsp. avium (MAA) of serotypes 1, 2 and 3 are infected animals (esp. birds), who shed MAA in different ways and thus contaminate the environment. The first aim of this work was to compare the efficiency of the diagnostic methods that are routinely used for the diagnosis of ATBC (skin test, serology and culture of faeces and eggs) in naturally infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…9 In the current study, Mah was not isolated from any fecal samples from bongo antelopes, and the possibility of a fecal-oral route of infection in these animals seems unlikely. Although the negative results of fecal cultivation may be due to the low numbers of Mah in the feces of the bongo antelopes or intermittent Mah shedding in feces, 15 the isolation of Mah from the feces of the okapi antelopes demonstrates the robustness of the culture method used in the present study.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…9 In the current study, Mah was not isolated from any fecal samples from bongo antelopes, and the possibility of a fecal-oral route of infection in these animals seems unlikely. Although the negative results of fecal cultivation may be due to the low numbers of Mah in the feces of the bongo antelopes or intermittent Mah shedding in feces, 15 the isolation of Mah from the feces of the okapi antelopes demonstrates the robustness of the culture method used in the present study.…”
mentioning
confidence: 77%
“…To assess the source of infection and possible risks to other antelopes and other animals from the nearby enclosures (especially okapis), a total of 117 environmental samples (soil, peat, water, bark mulch, feed, straw with urine, dust, and house flies [ Musca domestica ]) and 22 fecal samples from bongos and okapis were examined using culture 15 and subsequent PCR identification of isolates. 12 Mycobacterium avium subsp.…”
mentioning
confidence: 99%
“…Another interestingly finding reported in this study is the detection of MAA from the fecal sample of White Pelican ( Pelecanus onocrotalus) sample using culture and Black Hornbill ( Anthracoceros malayanus) using direct PCR. Although MAA has been reported in domestic hen [ 42 ], macaw [ 16 , 43 ], cockatoo [ 16 , 43 ], and commercial ducks [ 1 ] from different region of the world, to the best of our knowledge only one study [ 43 ] reported MAA from White Pelican but there is no published data from Black Hornbill.…”
Section: Discussionmentioning
confidence: 99%
“…hominissuis is pathogenic mainly to humans (31,35), while infections with M. avium subsp. avium are more typical for birds (11,35,(40)(41)(42), perhaps indicating why there was an increased susceptibility to M. avium subsp. hominissuis in these patients.…”
Section: Discussionmentioning
confidence: 99%